The Managers' Perceptions of Telework Implementation Requirements in the Algerian Companies: A Post Covid-19 Assessment - Riad BENGHEBRID (European Journal of Management Issues)
Purpose: The main purpose of the study was determining the basic requirements for implementing telework in Algerian companies after the Covid-19 pandemic, in order to establish it, and accordingly it become a prevailing management culture.